Syarat dan Mekanisme Impeachment Presiden dan/atau Wakil Presiden: Perspektif Hukum Konstitusi Indonesia - Setiawan, Risman (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
This study discusses the requirements and mechanisms for the Impeachment of the President and/or Vice President of the Republic of Indonesia from the perspective of Indonesian constitutional law, focusing on the possibility of impeaching Vice President Gibran Rakabuming Raka. In the 1945 Constitution of the Republic of Indonesia, the mechanism for the Impeachment of the President and/or Vice President is strictly regulated through Articles 7A and 7B, which require serious violations of the law such as treason against the state, corruption, bribery, other serious crimes, or disgraceful acts. The dismissal process begins with a proposal from the DPR, continues with an examination in the DPR then continues to the Constitutional Court, and ends with a decision by the MPR. Until now, there has been no legal evidence or official process stating that Vice President Gibran has met the requirements to be dismissed according to the constitution. Thus, dismissal can only be carried out if all stages of law and constitutional proof have been met. This study emphasizes the importance of maintaining the supremacy of the constitution in the Indonesian constitutional law system.